Trajectory of post-COVID brain fog, memory loss, and concentration loss in previously hospitalized COVID-19 survivors: the LONG-COVID-EXP multicenter study - Fernández-de-las-Peñas, César; Cancela-Cilleruelo, Ignacio; Rodríguez-Jiménez, Jorge; Arias-Navalón, José A.; Martín-Guerrero, José D.; Pellicer-Valero, Oscar J.; Arendt-Nielsen, Lars; Cigarán-Méndez, Margarita (Frontiers in Human Neuroscience, 2023)
Objective: To apply Sankey plots and exponential bar plots for visualizing the trajectory of post-COVID brain fog, memory loss and concentration loss in a cohort of previously hospitalized COVID-19 survivors. Methods: A sample of 1,266 previously hospitalized patients due to COVID-19 during the first wave of the pandemic were assessed at 8.4 (T1), 13.2 (T2) and 18.3 (T3) months after hospital discharge. They were asked about the presence of the following self-reported cognitive symptoms: brain fog (defined as self-perception of sluggish or fuzzy thinking), memory loss (defined as selfperception of unusual forgetfulness), and concentration loss (defined as self-perception of not able to maintain the attention). We asked for symptoms that individuals did not experience before and they attributed to the acute infection. Clinical and hospitalization data were collected from hospital medical Sankey plots of post-COVID cognitive symptoms 2 This is a provisional file, not the final typeset article records. Results: The Sankey plots revealed that the prevalence of post-COVID brain fog was 8.37% (n=106) at T1, 4.7% (n= 60) at T2, and 5.1% (n=65) at T3, whereas the prevalence of post-COVID memory loss was 14.9% (n=189) at T1, 11.4% (n=145) at T2, and 12.12% (n=154) at T3. Finally, the prevalence of post-COVID concentration loss decreased from 6.86% (n=87) at T1, to 4.78% (n= 60) at T2, and to 2.63% (n=33) at T3. The recovery exponential curves show a decrease trend visualizing that these post-COVID cognitive symptoms recovered the following years after discharge. The regression models did not reveal any medical record data associated with post-COVID brain fog, memory loss or concentration loss at long-term. Conclusion: The use of Sankey plots shows a fluctuating evolution of post-COVID brain fog, memory loss or concentration loss during the first years after the infection. In addition, exponential bar plots revealed a decrease prevalence of these symptoms during the first years after hospital discharge. No risk factors were identified in this cohort.